2015
DOI: 10.1093/mnras/stu2748
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared variations of R Coronae Borealis stars

Abstract: Mid-infrared photometry of R Coronae Borealis stars obtained from various satellites from IRAS to WISE has been utilized in studying the variations of the circumstellar dust's contributions to the spectral energy distribution of these stars. The variation of the fractional coverage (R) of dust clouds and their blackbody temperatures (T d ) have been used in trying to understand the dust cloud evolution over the three decades spanned by the satellite observations. In particular, it is shown that a prediction R∝… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…In Figure 11, we plot the periods of these stars against their effective temperatures. This figure is similar to Figure 32 of Lawson et al (1990) and Figure 15 of Rao & Lambert (2015). Clayton et al (2003) showed that most (if not all) RCB stars have winds.…”
Section: Pulsation Periods and Effective Temperaturessupporting
confidence: 88%
“…In Figure 11, we plot the periods of these stars against their effective temperatures. This figure is similar to Figure 32 of Lawson et al (1990) and Figure 15 of Rao & Lambert (2015). Clayton et al (2003) showed that most (if not all) RCB stars have winds.…”
Section: Pulsation Periods and Effective Temperaturessupporting
confidence: 88%
“…There are other R CrB stars which are known or suspected to pulsate. Rao and Lambert (2015) list 29. Most if not all of them have pulsation amplitudes which are even smaller than that of RY Sgr, so it will be almost impossible to study their pulsation with visual data.…”
Section: Discussionmentioning
confidence: 99%
“…These puffs can be detected in the IR. Recent studies pertaining to IR variability of RCB stars has found that the covering factor can vary from RCB star to RCB star and find an average covering factor of 0.28±0.04 for R CrB (García-Hernández, Rao & Lambert 2011b;Rao & Lambert 2015). Other studies find a higher covering factor (Hecht et al 1984;Clayton et al 1999).…”
Section: Mass Loss From a White Dwarf Merger?mentioning
confidence: 99%